PENERAPAN METODE UNIVERSAL KRIGING (UK) UNTUK PREDIKSI KONSENTRASI PARTICULATE MATTER 2.5 (PM2.5) DI KOTA BANDUNG - Putri, Salsabila Eka; Kusuma, Dianne Amor; Ruchjana, Budi Nurani (PATTIMURA UNIVERSITY, 2020)
The tendency of increasing industrial and population activities in the city of Bandung causes a decrease in air quality. One material that causes air pollution which is very dangerous for health is particulate matter 2.5 (PM2.5). Efforts to control and overcome PM2.5 concentration are carried out through measurements in several locations. However, due to limitations of measuring devices and costs, so not all locations in the city of Bandung can be measured PM2.5 concentration. PM2.5 concentration data tends not to be stationary. Therefore it is necessary to interpolate the PM2.5 concentration data using the Universal Kriging method. In this paper, the Universal Kriging method can be applied to predict PM2.5 concentrations in locations that are not sampled because the observed PM2.5 concentration data are spatial data that have different PM2.5 concentrations at each location. Data were analyzed with the help of software R 3.5.3 and ArcGIS 10.4 to create contour maps. Based on the prediction results of PM2.5 concentrations at locations that were not sampled, obtained a first order trend equation is better used to predict PM2.5 concentrations because it has a minimum Universal Kriging error variance value compared to the second order trend equation. The results showed that the location with high PM2.5 concentration was in the northwest of Bandung City. Contour maps show locations that have low to high PM2.5 concentrations